Mapping the undiscovered objects and sites in Lithuania - Jasiūnas, Justinas; Maneikaitė, Edita; Venckus, Paulius; Romanovas, Denis; Beconytė, Giedrė (Geodesy and Cartography, 2013)
Forlorn, uncared-for cultural or natural objects and sites fail to be included into lists of touristic attractions due to their obscurity, poor condition and communication and are usually visited by certain social groups (extreme adventure travellers, members of various subcultures and etc.). The analysis revealed a wide array of such objects and sites, which are unknown and not in very good condition, can be very different starting with manor houses, historic parks and gardens and finishing with airfields, open courses or dumping grounds. The goal of a pilot research project carried out at the National Centre of Remote Sensing and Geoinformatics “GIS-Centras” was to collect information on diverse objects and sites that are typically not included into official information sources and fall outside the tourist infrastructure network. The collected information will be published as a map service. The inventory of such undiscovered objects and sites and visualisation is one of the ways to encourage the interest of visitors, especially in regions that lack famous tourist attraction objects or beautiful landscapes. The paper describes solutions for the structure of the database, object acquisition technology, cartographic visualisation and publication of collected data as an online map at www.nemasinis.lt ...